Database design learning: A project-based approach organized through a course management system - Domínguez, César; Jaime, Arturo (Computers and education, 2010)
This paper describes an active method for database design learning through practical tasks development by student teams in a face-to-face course. This method integrates project-based learning, and project management techniques and tools. Some scaffolding is provided at the beginning that forms a skeleton that adapts to a great variety of student-proposed domain projects and emulates the real way of working in database design. We include a quasi-experimental study in which the results of five academic years are analyzed. The first three years a traditional strategy was followed and a course management system was used as material repository. The active method was introduced for the last two years and coexisted with the traditional one. The course management system greatly simplifies the management of the numerous documents produced, the description and scheduling of tasks, the identification of teams, as well as all communication needs. In this study we analyze aspects such as exam dropout rates, exam passing rates, exam marks, and class attendance. Students that followed this active learning approach obtained better results than those that followed a traditional strategy. Besides, the experience of the introduction of such a method in a student subgroup positively influenced the whole group.